Pengaruh Iklan cetak dan Iklan Online terhadap Kesadaran Merek City Branding Sparkling Surabaya: Studi pada Masyarakat di Surabaya - Kharisma Nur Masitha (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
By referring to the concept of brand awareness pyramid, pre-research activities have been conducted on 160 respondents, to try to measure the level of brand awareness in Sparkling Surabaya. Pre-research results indicate the level of brand awareness of the city, the city of Surabaya is at the top of the mind Top of Mind, for brand awareness Branding Sparkling city of Surabaya is still in Unaware of a Brand, meaning that at this level the community is less aware of the brand presence or brand Sparkling city Surabaya. The purpose of this study is to analyze and discuss the effect of print and online advertising on brand awareness of the City Branding Sparkling Surabaya. The population used in this study is the people of Surabaya who have seen print advertisements and City Branding Sparkling online advertisements in Surabaya. The sampling technique used is nonprobability sampling with the purposive sampling method. The number of samples used was as many as 150 respondents. The results showed that there was a significant positive effect of print advertisements (X1) and online advertisements (X2) on City Branding Sparkling Surabaya (Y) brand awareness. The highest coefficient value in the multiple linear regression analysis equations is owned by online advertising variables